Conserving living heritage site in Portuguese settlement, Melaka world heritage site: issues and conservation elements. Issue 1 (August 2021) - Jamaludin, I S; Seow, T W; Mat Radzuan, I S; Mohamed, S; Abas, M A
Abstract: A living heritage site symbolizes the integration between tangible and intangible cultural heritage. It has a traditional community, or a specific area in the environment of a traditional settlement. Rapid urban development poses significant threats to heritage sites, with deterioration and destruction of heritage by introducing pollution, political wars, growing tourism activities, and natural disasters. Conservation of living heritage is by accenting the role of the core community staying in traditional settlements within the heritage area. The city of Melaka was declared as World Heritage Site in 2008 and the government engaged in significant urban development to accommodate the increasing number of tourists landing, and it has threatened its heritage site. Such act jeopardised the core community of Portuguese Settlement with the risk of obliteration of its cultural heritage in the future and this is due to insufficient conservation of community's cultural heritage from soft infrastructure approaches. Hence, the purpose of this article is to highlight the issues faced by the Portuguese community and discuss elements of community participation, awareness, and stakeholder's involvement to conserve the community's cultural heritage. It is done by qualitative methods of interviews, and document analysis of relevant literature, reports and standards. The result reveals the main issues faced by the community are authenticity, vulnerability of modernisation and development hazard, and losing its community. The output of the paper would be beneficial to stakeholders, practitioners, and researchers to develop a sustainable community within the heritage site while maintaining its heritage value.